INTERPRETATION PUBLIC POLICY IN RECOGNITION AND ENFORCEMENT OF FOREIGN ARBITRAL AWARD IN INDONESIA TURN ASIDE THE LEGAL CERTAINTY - Amriani, Nurnaningsih (Brawijaya Law Journal, 2014)
Does not violate â€œpublic policy (public order/openbaare orde)â€ is the one of the main reasons for the recognition and enforcement of foreign arbitral award in Indonesia. It follow the rules of Article V of the New York Convention 1958 in which Indonesia ratified through Presidential Decree No. 34 of 1981. This article aims to provide a form of judge interpretation of the meaning of public order before and after the enactment of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, so there is no legal certainty. Therefore the meaning of "public policy" does not limit the scope described in the decree and the Arbitration Act, therefore the interpretation obtained by the decision of the Supreme Court who refused and received recognition of foreign arbitral award in Indonesia. Through the interpretation of this article, the parties involved in the arbitration agreement can predict whether their arbitration award may be given the recognition and implementation in Indonesia.